Ecological momentary interventions in social work: a psychological approach to enhancing client well-being - Cădariu, Ioana-Eva; Rad, Dana (Technium Social Sciences Journal, 2025)
Ecological Momentary Interventions (EMIs) are an exciting development in the provision of psychosocial and mental health services, providing real-time, context-aware therapeutic interaction via mobile technologies. In this paper, the application of EMIs in social work practice is discussed from a psychological viewpoint, with a focus on their potential for supporting increased client well-being, empowerment, and resilience. Grounded in recent research, we review the psychological mechanisms of EMI effectiveness, including self-monitoring, feedback loops, and cognitive-behavioral processes used in daily life settings. Applications of EMIs in crisis management, support of vulnerable populations, and prevention of mental health deterioration are critically examined. Ethical concerns, such as confidentiality, data protection, and client autonomy, are addressed alongside new technology developments, like AI-driven personalization. The article concludes by emphasizing EMIs' revolutionary potential in bridging gaps between traditional services and dynamic client needs. By embedding interventions within everyday life contexts, EMIs align with social work's and psychology's core values, promoting more immediate, personalized, and equitable care. Future directions highlight the need for inclusive design, rigorous ethical frameworks, and practitioner training to fully leverage the potential of EMIs across diverse practice settings.